POSITIVE LEADERSHIP: CONCEPTUAL FOUNDATIONS AND POSSIBILITIES OF APPLICATION IN THE STATE CIVIL SERVICE OF UZBEKISTAN - Kodirova Sharifakhon Asratulloevna (Journals Park Publishing, 2024)
This article is devoted to the study of the concept of positive leadership, its principles and potential for application in the management of the state civil service of Uzbekistan. The author examines the theoretical base, the main achievements of research in the field of positive psychology, and also gives an interpretation of the application of this approach in the context of modern challenges of public service. The possibilities of applying this approach in the conditions of Uzbekistan and solving difficulties through the introduction of positive leadership in management are also highlighted.
Keywords: Positive leadership, public civil service, motivation, personnel management, awareness, strengths, Uzbekistan.